Achieving change in primary care—causes of the evidence to practice gap: systematic reviews of reviews. (December 2015) - Lau, Rosa; Stevenson, Fiona; Ong, Bie; Dziedzic, Krysia; Treweek, Shaun; Eldridge, Sandra; Everitt, Hazel; Kennedy, Anne; Qureshi, Nadeem; Rogers, Anne; Peacock, Richard; Murray, Elizabeth
Abstract Background This study is to identify, summarise and synthesise literature on the causes of the evidence to practice gap for complex interventions in primary care. Design This study is a systematic review of reviews. Methods MEDLINE, EMBASE, CINAHL, Cochrane Library and PsychINFO were searched, from inception to December 2013. Eligible reviews addressed causes of the evidence to practice gap in primary care in developed countries. Data from included reviews were extracted and synthesised using guidelines for meta-synthesis. Results Seventy reviews fulfilled the inclusion criteria and encompassed a wide range of topics, e.g. guideline implementation, integration of new roles, technology implementation, public health and preventative medicine. None of the included papers used the term "cause" or stated an intention to investigate causes at all. A descriptive approach was often used, and the included papers expressed "causes" in terms of "barriers and facilitators" to implementation. We developed a four-level framework covering external context, organisation, professionals and intervention. External contextual factors included policies, incentivisation structures, dominant paradigms, stakeholders' buy-in, infrastructure and advances in technology. Organisation-related factors included culture, available resources, integration with existing processes, relationships, skill mix and staff involvement. At the level of individual professionals, professional role, underlying philosophy of care and competencies were important. Characteristics of the intervention that impacted on implementation included evidence of benefit, ease of use and adaptability to local circumstances. We postulate that the "fit" between the intervention and the context is critical in determining the success of implementation. Conclusions This comprehensive review of reviews summarises current knowledge on the barriers and facilitators to implementation of diverse complex interventions in primary care. To maximise the uptake of complex interventions in primary care, health care professionals and commissioning organisations should consider the range of contextual factors, remaining aware of the dynamic nature of context. Future studies should place an emphasis on describing context and articulating the relationships between the factors identified here. Systematic review registration PROSPEROCRD42014009410